2016
DOI: 10.5194/bg-13-3441-2016
|View full text |Cite
|
Sign up to set email alerts
|

Accurate and precise quantification of atmospheric nitrate in streams draining land of various uses by using triple oxygen isotopes as tracers

Abstract: Land use in a catchment area has significant impacts on nitrate eluted from the catchment, including atmospheric nitrate deposited onto the catchment area and remineralised nitrate produced within the catchment area. Although the stable isotopic compositions of nitrate eluted from a catchment can be a useful tracer to quantify the land use influences on the sources and behaviour of the nitrate, it is best to determine these for the remineralised portion of the nitrate separately from the unprocessed atmospheri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
64
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 34 publications
(74 citation statements)
references
References 72 publications
10
64
0
Order By: Relevance
“…The values and trends are consistent with prior empirical studies of 17 O wet at Rishiri between 2006 and 2007 and elsewhere in Japan (Tsunogai et al, 2016). These results also coincide well with model predictions (Alexander et al, 2009), which suggest that they indicate seasonal variation in the relative importance of oxidation of NO 2 by O 3 vs. OH in background, free tropospheric air.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…The values and trends are consistent with prior empirical studies of 17 O wet at Rishiri between 2006 and 2007 and elsewhere in Japan (Tsunogai et al, 2016). These results also coincide well with model predictions (Alexander et al, 2009), which suggest that they indicate seasonal variation in the relative importance of oxidation of NO 2 by O 3 vs. OH in background, free tropospheric air.…”
Section: Discussionsupporting
confidence: 89%
“…Prior to isotopic analysis we reanalyzed nitrate and nitrate concentrations in the samples and found that differences between these and the original concentration measurements were < 10 %. For isotopic analysis, nitrite and nitrate in each filtrate sample was converted to N 2 O using chemical conversion (McIlvin and Altabet, 2005) with slight modification (Tsunogai et al, , 2016. Isotopic analysis of nitrite alone was also performed on samples with nitrite concentrations > 5.0 % of the total nitrite plus nitrate concentrations (McIlvin and Altabet, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations